Relationship between sources and manifestations of stress among faculty members in Isabela State University - Helena B. Florendo; Annaliza R. Hernando (International Journal of Public Health Science (IJPHS), 2021)
Stress is inevitable in any workplace. Stressed teachers in every school are prone to exhaustion and commit errors. In the Philippines, few studies have been discussed due to stress among faculty members, especially in tertiary education. In this study, the researchers shed light on sources, manifestations, and levels of stress, and discovered the relationship between sources and their manifestations among faculty members of the eight colleges of the Isabela State University-Main Campus. Data were randomly collected from 165 respondents, through the Teacher Stress Inventory developed by Fimian. Data revealed that the main sources and manifestations of stress by the respondents were Work-related and Professional Investment, and Fatigue Manifestations. The level of stress among the respondents was moderate. Likewise, the sources and manifestations of stress were found significantly correlated to each other. Results of the study press on the development of a proposed Stress Management Program supportive and essential in managing and coping stress of the faculty member